2014
DOI: 10.4049/jimmunol.1302244
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ability of Surface and Endosomal TLRs To Induce CD8 T Cell Responses In Vivo

Abstract: Toll Like Receptor (TLR) activation on dendritic cells (DCs) induces DC maturation and secretion of pro-inflammatory cytokines, both of which are important for activation and differentiation of CD4 T cells. The importance of TLR activation on DCs for CD8 T cell responses is less clear. Here, we tested the ability of different TLRs to regulate CD8 T cell responses to pathogens. We found that although all TLRs are able to induce CD8 T cell activation in vitro, there are profound differences in their ability to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 60 publications
3
34
0
Order By: Relevance
“…Also, for prime-boost group animals, the double-stranded RNA receptor TLR3 was expressed exclusively in protected animals after the first challenge, whereas the expression of surface TLR4 was unique to delayed-viremic animals after the first challenge. It was previously shown that only TLR3 enhances CD8 T cell responses in vivo and that TLR2 and TLR4 activation may suppress pathogen-induced CD8 T cell responses (32). This suggests that TLR4-mediated signaling may possibly act as an antagonist to CD8 ϩ T cell responses during challenge, despite the presence of these responses prior to challenge.…”
Section: Discussionmentioning
confidence: 70%
“…Also, for prime-boost group animals, the double-stranded RNA receptor TLR3 was expressed exclusively in protected animals after the first challenge, whereas the expression of surface TLR4 was unique to delayed-viremic animals after the first challenge. It was previously shown that only TLR3 enhances CD8 T cell responses in vivo and that TLR2 and TLR4 activation may suppress pathogen-induced CD8 T cell responses (32). This suggests that TLR4-mediated signaling may possibly act as an antagonist to CD8 ϩ T cell responses during challenge, despite the presence of these responses prior to challenge.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, Mercier et al showed that TLR2 cooperate with NOD-containing protein 1 (NOD1) to enhance TCR mediated activation and can serve as alternative co-stimulatory receptor in CD8 + T cells (106). CD8 + T cells also express intracellular TLRs such as TLR3, TLR9 which are more potent in inducing CD8 + T cell activation in vivo (107). …”
Section: Toll Like Receptor and Immune Cellsmentioning
confidence: 99%
“…TLRs control activation of the innate and adaptive immune responses, which is generally produced by inducing the maturation of DCs [44, 45]. How Loxoribin signals regulate the suppressive function of Treg cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%